Isolation and Culture of Marine Microalgae (Chaetoceros sp.) as Life Feed - Siti Zaharah, Binti Saad (Universiti Malaysia Sarawak (UNIMAS), 2007)
The culture of micro algae as life feed has long being practiced to support the growth of cultured organisms in aquaculture industry. Diatom, Chaetoceros sp. were successfully isolated from the water sample from Asajaya. It has been cultured in two types of medium in starter culture, KW 104 21 medium and SW II medium with the same cells density, 1.0 x cells/ml while batch culture has been carried out using KW 21 medium with starting cells density, 1.0 x 104 cells/ml. The batch culture was established from the starter culture ofKW 21 medium and SW II medium to compare the growth rates of Chaetoceros sp. The starting cells density for batch culture was 1.0 x 104 cells/ml. The growth curves for both starter and batch culture has been determined. The starter media, SW II gave higher density of cells in both starter and batch culture. The highest cells density of Chaetoceros sp. in starter culture was 5.6400 x 106 cells/ml while the highest cells densit:y in batch culture was 14.4300 x 106 cells/ml. Further study on Chaetoceros sp. in the future should be carried out in order to determine its potential in aquaculture industry.